2018
DOI: 10.3390/antiox7040053
|View full text |Cite
|
Sign up to set email alerts
|

Betalains in Some Species of the Amaranthaceae Family: A Review

Abstract: Natural pigments are largely distributed in the plant kingdom. They belong to diverse groups, with distinct biochemical pathways. Betalains with colours that range from yellow to red-violet can de divided into two main subgroups: betaxanthins and betacyanins. These types of pigments are confined into 13 families of the order Caryophyllales and in some genera of higher fungi (Amanita muscaria, Hygrocybe and Hygrophorus). The Amaranthaceae family includes diverse genera in which betalains are present: Alternanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 225 publications
(381 reference statements)
3
85
0
1
Order By: Relevance
“…Stagnari, Galieni, Speca, & Pisante (2014) reported an increase of betacyanin by > 90% and > 70% in plants watered at 50% and 30% field capacity respectively compared to that of control plants (100% field capacity). The betacyanins in plants under water stress, as secondary metabolites, may function as scavengers of ROS, photoprotectants, and stress signals (Yang et al, 2018) and even as osmoregulants (Miguel, 2018).…”
Section: Copyright © 2019 Universitas Brawijayamentioning
confidence: 99%
“…Stagnari, Galieni, Speca, & Pisante (2014) reported an increase of betacyanin by > 90% and > 70% in plants watered at 50% and 30% field capacity respectively compared to that of control plants (100% field capacity). The betacyanins in plants under water stress, as secondary metabolites, may function as scavengers of ROS, photoprotectants, and stress signals (Yang et al, 2018) and even as osmoregulants (Miguel, 2018).…”
Section: Copyright © 2019 Universitas Brawijayamentioning
confidence: 99%
“…The supplement used in our study consisted of a concentrate that was standardized to contain 12.5 mg of betalains separated from nitrates and sugars. Therefore, the absence of sugar, in addition to encapsulation, might have enhanced the absorption and bioavailability of the betalains (Miguel, 2018;Tesoriere et al, 2004), which could explain some of the observed discrepancies in our study. It is important to point out that our study examined muscle damage of the elbow flexors, not the knee extensors.…”
Section: Previous Work Bymentioning
confidence: 71%
“…Betalains are water-soluble nitrogenous pigments that are naturally occurring compounds that give colours to plants and have strong antioxidant activity (Miguel 2018). The health-promoting activities of betalains have been extensively studied in the context of their anticancer, anti-in ammatory, hepatoprotective and have been commercialized as dietary supplements and used in food colorants in the food industry (Kaur et al 2018).…”
Section: Keypointsmentioning
confidence: 99%